HISTOLOGICAL EFFECT OPTIMIZATION COMBINATION OF BACILLUS SPHAERICUS 2362 AND BACILLUS THURINGIENSIS SUBSP. ISRAELENSIS IN MIDGUT OF CULEX QUINQUEFASCIATUS RESISTANCE - Tjokropranoto, Rita; Hanggono Acmad, Tri; Sutedja, Endang; Tjahjani, Susy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the study was to analyze pore‑forming at Culex quinquefasciatus resistant larvae midgut and analyze optimization ratio after treatment using combination Bacillus thuringiensis var. israelensis (Bti) and Bacillus sphaericus (Bs) 2362. Methods: This research was an experimental study. C. quinquefasciatus larvae were divided into 10 groups. The Group I until VII had treatment by the various concentration of combination Bti and Bs 2362, treatment Group VIII as a positive control, Group IX as a negative control, and Group X as a single Bs 2362. All of the treatment groups were examined for the histological effect of C. quinquefasciatus larvae midgut by hematoxylin eosin. The lowest lethal concentration 50% (LC Results: The lowest LC 50 50 ) was a standard optimization ratio of combination Bti and Bs 2362. LC 50 was analyzed by probit. was 2.274 part a million (ppm) at Group I was the optimization ratio. Various combination treatments Group I until VII were shown pores at C. quinquefasciatus larvae midgut after treatment by a combination of Bti and Bs 2362. Conclusion: Combination of Bti and Bs 2362 was shown pores at C. quinquefasciatus larvae midgut, and optimization ratio was shown in Group I. Keywords: Bacillus thuringiensis var. israelensis, Bacillus sphaericus 2362, Culex quinquefasciatus midgut.